Effect of cefepime (BMY-28142) on the hemolytic and bactericidal activity of serum in vivo and in vitro (Revista Española de Fisiología, 1994)
The present study was undertaken to determine whether cefepime (BMY-28142) could influence the hemolytic and bactericidal activity of serum both in vivo and in vitro. For the in vivo studies, mice (Swiss aged 15 +/- 2 weeks) were studied before and 1, 2, 4, 8, and 12 h after an intramuscular injection of 200 mg/kg of cefepime. Likewise, another group of mice were injected for 7 days with a daily injection of the same dose as before, and sacrificed one hour after the last injection. For the in vitro studies, samples were incubated in the presence and absence of cefepime (1/2, 1/4 and 1/8 MIC against Staphylococcus aureus) (2.5, 1.25 and 0.625 mg/l respectively). The results indicate that cefepime at sublethal concentrations increases the bactericidal activity of serum both in vivo and in vitro against S. aureus, but does not significantly modify the hemolytic activity of the complement.